The onset of PI3K‐related vascular malformations occurs during angiogenesis and is prevented by the AKT inhibitor miransertib. Issue 7 (13th June 2022) - Kobialka, Piotr; Sabata, Helena; Vilalta, Odena; Gouveia, Leonor; Angulo‐Urarte, Ana; Muixí, Laia; Zanoncello, Jasmina; Muñoz‐Aznar, Oscar; Olaciregui, Nagore G; Fanlo, Lucia; Esteve‐Codina, Anna; Lavarino, Cinzia; et al.
Abstract: Low‐flow vascular malformations are congenital overgrowths composed of abnormal blood vessels potentially causing pain, bleeding and obstruction of different organs. These diseases are caused by oncogenic mutations in the endothelium, which result in overactivation of the PI3K/AKT pathway. Lack of robust in vivo preclinical data has prevented the development and translation into clinical trials of specific molecular therapies for these diseases. Here, we demonstrate that the Pik3ca H1047R activating mutation in endothelial cells triggers a transcriptome rewiring that leads to enhanced cell proliferation. We describe a new reproducible preclinical in vivo model of PI3K‐driven vascular malformations using the postnatal mouse retina. We show that active angiogenesis is required for the pathogenesis of vascular malformations caused by activating Pik3ca mutations. Using this model, we demonstrate that the AKT inhibitor miransertib both prevents and induces the regression of PI3K‐driven vascular malformations. We confirmed the efficacy of miransertib in isolated human endothelial cells with genotypes spanning most of human low‐flow vascular malformations. SYNOPSIS: This work describes a robust preclinical model of PI3K‐driven vascular malformations using the postnatal mouse retina. We show that AKT inhibition by miransertib is an effective therapeutic strategy for these diseases. Pik3ca H1047R mutation in endothelial cells leads to enhanced cell cycle progression. Active angiogenesis is required for the formation of PI3K‐driven vascular malformations. PI3K‐driven vascular malformations are prevented and regressed upon miransertib treatment. Abstract : This work describes a robust preclinical model of PI3K‐driven vascular malformations using the postnatal mouse retina. We show that AKT inhibition by miransertib is an effective therapeutic strategy for these diseases.